2003
DOI: 10.1097/00000542-200301000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Peripheral Endogenous Opioid Analgesia by Central Afferent Blockade

Abstract: These findings suggest an interplay of central and peripheral mechanisms of pain control. An effective central inhibition of pain apparently signals a reduced need for recruitment of opioid-containing immune cells to injured sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…In addition, the recruitment of opioid-containing cells is dependent on neurokinin-1 receptors (which bind substance P) (Rittner et al, 2007b), on sensory and sympathetic neurons (Kager et al, 2010), and may be regulated by adhesion to neurons (Hua et al, 2006). Central mechanisms also play a role because intrathecally administered analgesic doses of morphine led to a decreased number of END-positive leukocytes in inflamed rat paws (Schmitt et al, 2003). This was confirmed in a clinical study using epidural analgesia in patients undergoing surgery (Heurich et al, 2007).…”
Section: Migration Of Opioid Peptide-producing Cells Tomentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the recruitment of opioid-containing cells is dependent on neurokinin-1 receptors (which bind substance P) (Rittner et al, 2007b), on sensory and sympathetic neurons (Kager et al, 2010), and may be regulated by adhesion to neurons (Hua et al, 2006). Central mechanisms also play a role because intrathecally administered analgesic doses of morphine led to a decreased number of END-positive leukocytes in inflamed rat paws (Schmitt et al, 2003). This was confirmed in a clinical study using epidural analgesia in patients undergoing surgery (Heurich et al, 2007).…”
Section: Migration Of Opioid Peptide-producing Cells Tomentioning
confidence: 87%
“…Thus, adhesion molecules have an impact on pain by modulating the extravasation of opioid producing immune cells and/or their adhesion to sensory neurons. In addition, central mechanisms apparently influence the migration of opioid-containing cells and endogenous analgesia in peripheral injured tissue (Schmitt et al, 2003;Heurich et al, 2007).…”
Section: Intrinsic Induction Of Opioid Peptide Release From Inflammatmentioning
confidence: 99%
“…Endogenous opioids may act by modulating pain at peripheral and central levels (13). Many studies have demonstrated an increase in the plasma levels of endogenous opioids, mostly β-endorphin, during and after aerobic exercise (5); however, only a few studies have investigated alterations in this parameter when resistance exercise was involved, with equivocal results.…”
Section: Discussionmentioning
confidence: 99%
“…catheterization was performed as described elsewhere with slight modifications (Schmitt et al, 2003;Strkson et al, 1996). Briefly, an incision was made at the L3-L4 level.…”
Section: Surgery To Implant Icv or It Guide Cannulamentioning
confidence: 99%